The Application of Biofertilizer on Growth And Yield of Melon Varieties (Cucumis Melo L.) - Safwandi, Safwandi; Hanani, Fadli; Yusuf N, Muhammad; Jamidi, Jamidi; Hafifah, Hafifah; Ismadi, Ismadi (Yayasan Pertanian Tropika Indonesia (YPTI), 2021)
Melon (Cucumis melo L.) is one of potential horticultural crop in Indonesia. Unfortunately, melon production is currently unable to meet national demand. The objective of this study was to investigate the effect of biofertilizer, varieties and interaction between the dose of biofertilizer and varieties on the growth and yield of melons. The study was conducted in January-April 2021 at Paloh Lada Village, Dewantara District and the Laboratory of Agriculture Faculty, Universitas Malikussaleh. These experiments were arranged in a Factorial Randomized Block Design (RBD) with two factors. The first factor was biofertilizer (P) consisting of 4 levels: P0 (0 ml/L), P1 (5 ml/L), P2 (10 ml/L) and P3 (15 ml/L) and the second factor was melon varieties (V): V1 (F1 Pertiwi Anvi) and V2 (F1 Action 88). There was 8 treatment combinations with 3 replications, resulted in 24 experimental units. The interaction between biofertilizers and varieties gave significant effect on the growth and yield of melon, while the interactions between bio fertilizer did not differ on all variables observed. The application of biological fertilizer 10 ml/L on V1 variety (F1 Pertiwi Anvi) is recommendable. There was an interaction between of biological fertilizers and melon varieties on the total dissolved solids (Brix %).